2007
DOI: 10.1017/s1751731107303467
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rabbit age on in vitro caecal fermentation of starch, pectin, xylan, cellulose, compound feed and its fibre

Abstract: In vitro gas production kinetics of six different substrates, pectin (PEC), xylan (XYL), starch (STA), cellulose (CEL), commercial compound feed (FEED; 201 g crude protein per kg, 155 g crude fibre per kg, 334 g neutral-detergent fibre (NDF) per kg and 190 g acid-detergent fibre (ADF) per kg) and an NDF prepared from commercial compound feed (NDF FEED ) were determined using the caecum contents of weaned rabbits (36 days of age) and of rabbits at slaughter age (78 days of age) as inoculums. The cumulated gas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
11
1
7
Order By: Relevance
“…According to Marounek et al (1995) and Lavrencic (2007), the caecal microbiota of 28-d old rabbits is limited with respect to adult animals and it is specialized in the fermentation of soluble fibrous carbohydrates (such as fructans, galactans, β-glucans and pectic substances; Hall et al, 1997). Consequently, the type of dietary f ibre could be important to promote the growth of beneficial microbiota in order to improve the competitive exclusion.…”
Section: Fibrementioning
confidence: 99%
“…According to Marounek et al (1995) and Lavrencic (2007), the caecal microbiota of 28-d old rabbits is limited with respect to adult animals and it is specialized in the fermentation of soluble fibrous carbohydrates (such as fructans, galactans, β-glucans and pectic substances; Hall et al, 1997). Consequently, the type of dietary f ibre could be important to promote the growth of beneficial microbiota in order to improve the competitive exclusion.…”
Section: Fibrementioning
confidence: 99%
“…CHANG et al (2001) suggested that the current fiber of the diets based on the total NDF content can hardly predict the requirements for dietary fiber in rabbits due to the complex chemical composition of the total dietary fiber and its multiple interactions with the microbial caecal ecosystem. For this reason the use of in vitro gas production techniques could allow the adequate characterization of feed fermentation in the caecum of post-gastric fermenters such as rabbits (LAVRENČIČ, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Manipulations and selection of animals and the preparation of inoculum were performed according to the methods described by Calabro et al (1999) and Lavrenčič (2007) (Calabro et al, 1999). The animals were sacrificed between 8:00 and 8:30 h and the caeca were isolated by tying off the two extremities with nylon string to prevent movement of the digesta.…”
Section: Substrates and In Vitro Fermentationmentioning
confidence: 99%
“…Feed with higher contents of pectic substances increased viscosity in small intestine (Volek et al, 2005), improved gut barrier function and ileal digestibility of starch and reduced caecal frequency of detection of Clostridium perfringens (Gómez-Conde et al, 2007), increased caecal biomass (Jehl and Gidenne, 1996), short chain fatty acids (Jehl and Gidenne, 1996;García et al, 2000;Marounek et al, 2007) and in vitro gas production (Marounek et al, 1997;Lavrenčič, 2007) and decreased mortality in rabbits (Gidenne, 2003;Gómez-Conde et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation